Gender and Sport Changes and Challenges - Pfister, Gertrud; Sisjord, Mari Kristin (2013)
This volume covers current issues, cutting-edge debates and new knowledge on women and sport. The range of topics extends from female coaches and women in sport to sexual harassment, from snowboarders to schoolgirls, and from physical education to football. The aim of this book is to provide an overview of the current debates on gender and sport from a women's perspective, to share new knowledge about important issues, in particular about gender (in)equalities, and to present insights into the causes and effects of the debates and developments in the arena of women's sport. A special focus in all chapters will be on the perspective of change, and backgrounds, reasons and effects of gender arrangements will be analyzed by scholars who made major contributions to the development of a new gender order in sport and society. Other authors are younger scholars with new perspectives and approaches - who represent the new generation of gender researchers.